2018
DOI: 10.1080/09553002.2018.1450533
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles mediate low dose ionizing radiation-induced immune and inflammatory responses in the blood

Abstract: Low and high dose effects overlapped both in EV-mediated alterations in signaling pathways leading to RIBE and in their systemic manifestations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 74 publications
1
32
0
Order By: Relevance
“…Several studies support the involvement of exosomes in mediating RIBE in vivo and in vitro [29,30,37,[53][54][55]. Bystander signals can be communicated through exosomes that can result in functional changes in target cells either by receptor-mediated interactions or by transfer of various bioactive molecules such as proteins, mRNA, miRNA or bioactive lipids carried by exosomes [56,57].…”
Section: Discussionmentioning
confidence: 92%
“…Several studies support the involvement of exosomes in mediating RIBE in vivo and in vitro [29,30,37,[53][54][55]. Bystander signals can be communicated through exosomes that can result in functional changes in target cells either by receptor-mediated interactions or by transfer of various bioactive molecules such as proteins, mRNA, miRNA or bioactive lipids carried by exosomes [56,57].…”
Section: Discussionmentioning
confidence: 92%
“…When RIBE is manifested by a release of cytokines, a COX-2-dependent pathway mediated by FasL and TNF-α 50,51 , releasing NO by irradiated cells, triggers the inflammatory response in un-irradiated cells through the p38 pathway 52 . Additionally, several studies have demonstrated that ELV are involved in mediating RIBE in cultured cells 31–34,37–39 and under in vivo conditions 35,36 . These studies suggest that inflammatory responses are involved in mediating RIBE signals.…”
Section: Discussionmentioning
confidence: 99%
“…Radiation-induced bystander effects (RIBE) consists of radiation induced adaptive responses [89], low-dose hypersensitivity [90], damage in DNA such as micronuclei formation, mutations, sister chromatid exchanges, modified gene expression, alteration in the miRNA profile, induced oxidative stress, and cell death [10,11,91,92,93,94,95]. RIBE emerge in non-irradiated cells that have received damaging signals from directly irradiated cells via intercellular communication [96,97,98,99].…”
Section: Evs and Radiationmentioning
confidence: 99%
“…However, data on radiation-induced changes in EV content is limited [9,10,17,91]. It was demonstrated that EV mediated miRNA (e.g., miR-21, miR-34c) transfer plays important role in RIBE [9,10,11], and proteins could also be important [110].…”
Section: Evs and Radiationmentioning
confidence: 99%